Well dispersed MoC quantum dots in ultrathin carbon films as efficient co-catalysts for photocatalytic H2 evolution. Issue 39 (25th September 2018) - Gao, Fan; Zhao, Yan; Zhang, Lulu; Wang, Bo; Wang, Yaozhu; Huang, Xueyan; Wang, Kaiqiang; Feng, Wenhui; Liu, Ping
Abstract : The proposed mechanism of photocatalytic reaction using a MoC-QDs/C/ZIS composite under visible light irradiation. Abstract : As a promising alternative to Pt, molybdenum carbides have been widely used in many domains. Herein, we develop a co-catalyst with a 2D lamellar structure, in which MoC quantum dots are embedded in a carbon membrane uniformly (MoC-QDs/C). With the introduction of MoC-QDs/C, the flower-like MoC-QDs/C/ZnIn2 S4 composite shows an unprecedented enhancement of photocatalytic performance, compared with that of pure ZnIn2 S4 . The optimal hydrogen generation rate of MoC-QDs/C/ZnIn2 S4 is almost 48 times as much as that of pure ZnIn2 S4 . Besides, the enhancement mechanism is also demonstrated that MoC-QDs/C can accelerate carriers' separation and decrease the overpotential of hydrogen evolution effectively during the photocatalytic water splitting process. Moreover, this study not only provides a high-efficiency and potential co-catalyst for photocatalytic H2 production, but also is expected to come up with a new design scheme for a transition metal carbide-containing co-catalyst.